Protein-altering and regulatory genetic variants near GATA4 implicated in bicuspid aortic valve - Bo Yang (Nature Portfolio, 2017)
Bicuspid aortic valve (BAV) is the most common human congenital cardiovascular malformation. Here, the authors perform a genome-wide association study for BAV and identify risk variants in the gene region of cardiac-specific transcription factor GATA4 and implicate GATA4 in heart valve development.